Physiologically-based pharmacokinetic modeling of tamoxifen and its metabolites in women of different CYP2D6 phenotypes provides new insight into the tamoxifen mass balance - Dickschen, Kristin; Willmann, Stefan; Thelen, Kirstin; Lippert, Jörg; Hempel, Georg; Eissing, Thomas (Frontiers in Pharmacology, 2012)
Tamoxifen is a first-line endocrine agent in the mechanism-based treatment of estrogen receptor positive (ER+) mammary carcinoma and applied to breast cancer patients all over the world. Endoxifen is a secondary and highly active metabolite of tamoxifen that is formed among others by the polymorphic cytochrome P450 2D6 (CYP2D6). It is widely accepted that CYP2D6 poor metabolizers (PM) exert a pronounced decrease in endoxifen steady-state plasma concentrations compared to CYP2D6 extensive metabolizers (EM). Nevertheless, an in-depth understanding of the chain of cause and effect between CYP2D6 genotype, endoxifen steady-state plasma concentration, and subsequent tamoxifen treatment benefit still remains to be evolved. In this context, physiologically-based pharmacokinetic (PBPK)-modeling provides a useful tool to mechanistically investigate the impact of CYP2D6 phenotype on endoxifen formation in female breast cancer patients undergoing tamoxifen therapy. It has long been thought that only a minor percentage of endoxifen is formed via 4-hydroxytamoxifen. However, the current investigation supports very recently published data that postulates a contribution of 4-hydroxytamoxifen above 20 % to total endoxifen formation. The developed PBPK-model describes tamoxifen PK in rats and humans. Moreover, tamoxifen metabolism in dependence of CYP2D6 phenotype in populations of European female individuals is well described, thus providing a good basis to further investigate the linkage of PK, mode of action, and treatment outcome in dependence of factors such as phenotype, ethnicity or co-treatment with CYP2D6 inhibitors.